DESIGNING ACCOUNTING INFORMATION SYSTEM FOR TRADING SMES: EMPIRICAL AND ISLAMIC INTEGRATION APPROACH - Yuniarti Hidayah Suyoso Putra; Sri Yati (Universitas Airlangga, 2018)
This research aims to describe the implementation of the accounting information system in the Small and Medium Enterprises (SMEs) which engaged in trading activities and provide recommendations to develop the accounting information system to support SMEs regarding best practices day to day operations and business side in Islam. The research uses mixed methods that attempt to bring together quantitative data and qualitative data to obtain a comprehensive analysis of the research problems. Trading SMEs have become the focused of research. Data collection are through observation, interviews, and documentation techniques. The analysis was performed using the accounting information system design regarding best practices and the business side of Islam. The results showed the sales process in trading SME used cash basis. The results analysis of weaknesses and strength of the accounting information system performance indicates that trading SMEs require the improvement concerning organizational structure, job descriptions, and internal controls related to inventory and fixed asset management. These results are used as a foundation to propose the new design of accounting information system without repeating the same mistakes in achieving corporate goals